Folate and Borneol Modified Bifunctional Nanoparticles for Enhanced Oral Absorption - Yifan Yang; Yunzhi Yin; Jun Zhang; Tiantian Zuo; Xiao Liang; Jing Li; Qi Shen (MDPI AG, 2018)
Oral delivery is considered the preferred route of administration due to its convenience and favorable compliance. Here, docetaxel (DTX) loaded polylactic-co-glycolic acid (PLGA) nanoparticles, coated with polyethyleneimine-folic acid (PEI-FA) and polyethyleneimine-borneol (PEI-BO), were designed to enhance oral absorption (FA/BO-PLGA-NPs). The FA/BO-PLGA-NPs were spherical and smooth with an average size of (137.0 ± 2.1) nm. Encapsulation efficiency (EE%) and drug loading (DL%) were (80.3 ± 1.8)% and (2.3 ± 0.3)%, respectively. In vitro release studies showed that approximately 62.1% of DTX was released from FA/BO-PLGA-NPs in media at pH 7.4. The reverted gut sac method showed that the absorption of FA/BO-PLGA-NPs in the intestines was approximately 6.0 times that of DTX. Moreover, cellular uptake suggested that the obtained FA/BO-PLGA-NPs could be efficiently internalized into Caco-2 cells via FA-mediated active targeting and BO-mediated P-glycoprotein (P-gp) inhibition. Pharmacokinetics study demonstrated that after oral administration of DTX at a dose of 10 mg/kg in FA/BO-PLGA-NPs, the bioavailability of FA/BO-PLGA-NPs was enhanced by approximately 6.8-fold compared with that of DTX suspension. FA/BO-PLGA-NPs caused no obvious irritation to the intestines. Overall, the FA/BO-PLGA-NP formulation remarkably improved the oral bioavailability of DTX and exhibited a promising perspective in oral drug delivery.